The Narrative Syntax of the E. Pashkovskyi’s Prosaic Texts (Linguostylistic Studies, 2017)
The article elucidates the notion of narrative in terms of linguostylistics and literary text linguistics. The emphasis is laid on the case study of the narrative syntax in the works by E. Pashkovskyi, particularly the most frequently used syntactic units and the peculiarities of the narrative structure including its role in the text creation. Attention is focused on revealing the dynamism and the author’s intentions semantics. The key findings of the study prove that the peculiarity of E. Pashkovskiy’s individual style is his unalterable commitment to macrosyntax – superlong sentences, multi-word structures. The author’s most preferential syntactical devices are amplification, repetitions, polysyndeton. The narrative syntax of the writer is based on the amplification of the predicates, subjects, adverbial modifiers, attributes, and repetitions of set expressions or phrases. It has been revealed that polysyndeton emphasizes the stylistic semantics of homogeneous subjects. E. Pashkovsky's narrative strategy is related to the author's individual type of word interconnections in the sentence: the subject and mismatching form of attribute, the postposition of homogeneous attributes.
Keywords: narrative text; narrative syntax; literary text; amplification; repetition; polysyndeton